Application Of Hybrid Learning Methods To Increase The Activeness Of Grade 3 Students Of SD Negeri 0512 Bonal Jae Batu - Mawaddah Pasaribu; Rinja Efendi; Elvina Elvina (STKIP Rokania Pasir Pangaraian, 2022)
The purpose of this study is to increase student learning motivation. Questions shared with parents and surveyed found that all students were tired of distance learning. The learning approach to improving student activity is combined with distance learning. Hybrid learning is a combination of online (in-network) and offline (off-network). This learning method was adopted because learning is more diverse. Students can observe/experiment/work on projects in the home environment after acquiring the material in an online format. Students are not tied to screens and module books, but students are more enthusiastic about activities around the house with family. This research is a class action study of 23 grade 3 students of SD Negeri 0512 Bonal Jae Batu. The study was conducted in 2 cycles with 2 sessions per cycle. Each session consists of 4 stages, namely planning, implementation, observation and reflection. The implementation of the research phase accommodates distance learning, which is carried out separately because the students are in their respective homes. Based on the results of the study, an average of 78.26% of students were active from 23 students in cycle I, and an average of 91.30% in cycle II. Therefore, the combined distance learning approach can increase student activity by 13.04% during the Covid-19 prevention period for grade 3 of SD Negeri 0512 Bonal Jae Batu